New national and regional biological records for Finland 7. Contributions to Bryophyta and Marchantiophyta - Riikka Juutinen; Tauno Ulvinen; Kimmo Syrjänen; Timo Kypärä; Tuomo Kuitunen; Ari Parnela; Raimo Heikkilä; Markku Suoknuuti; Tarja Marsh; Harri Arkkio; Xiaolan He; Sanna Huttunen; et al. (Societas pro Fauna et Flora Fennica, 2022)
Three species of mosses (Bryophyta: Philonotis yezoana, Protobryum bryoides, Rhynchostegium
murale) and one of liverworts (Marchantiophyta: Moerckia flotoviana) are presented new for Finland.
Timmia megapolitana, previously thought to be regionally extinct, is reported to being found
again. New records in biogeographical provinces for 82 species of mosses and 34 species of liverworts
are listed. Finally, 8 occurrences in provinces are removed due to misidentifications or
missing specimens.